The Relationship Between Emotion Regulation And Teacher Work Motivation At Vocational High School - San Putra; Aman Simaremare; Risma Dina (Universitas Islam Bunga Bangsa Cirebon, 2024)
This research aims to determine the relationship between emotional regulation and teacher work motivation. This research was conducted at Putra Anda Binjai Vocational School. This research method uses non-test techniques, namely in the form of questionnaires. The sample for this research consisted of 80 teachers. The sampling technique was carried out by total sampling. The research results show that the r count is 0.803, with a p value = 0.000. Because p < 0.05 (0.000 < 0.05), Ha is accepted and Ho is rejected, so it can be interpreted that there is a positive and significant relationship between emotional regulation and teacher work motivation. The resulting determinant coefficient is r2 = 0.845, so it can be seen that emotional regulation has an influence of 84.5% on teacher work motivation and another 35.5% is influenced by other factors.